Analysis of the crown fractures and crown-root fractures due to dental trauma assisted by the Integrated Clinic from 1992 to 2002 - Castro, JCM; Poi, Wilson Roberto [UNESP]; Manfrin, T. M.; Zina, L. G. (Blackwell Munksgaard, 2005)
The purpose of this study was to analyze crown fractures and crown-root fractures due to dentoalveolar trauma, treated in the Integrated Clinic comprehensive dental care at Aracatuba School of Dentistry (UNESP), from January 1992 to July 2002. The data were obtained from files of trauma cases. on the analysis period, 293 patients had crown fractures or crown-root fractures, in 605 teeth. Sixty-nine percent were males and 31% were females. Adolescents between 11 and 18 years old were the most prevalent group (41.6%) and the maxillary arch was the most commonly traumatized (83%). The most commonly affected tooth was the maxillary central incisor (58.3%). The most frequent causes were falls from bicycles (30.8%). It was concluded that the reality of the local service is similar to the published data.
Keywords: tooth fractures; facial injuries; comprehensive dental care